Yria (western Naxos Island, Greece): Sea level changes in Upper Holocene and palaeogeographical reconstruction. - Evelpidou, N.; Pavlopoulos, K.; Vassilopoulos, A.; Triantafyllou, M.; Vouvalidis, K.; Syrides, G. (Geodynamica Acta, 2010)
The Saint Georgios coastal zone, located at the W coast of Naxos, the largest island of the Central Aegean Sea, was investigated in order to determine the palaeo-geography, sea level changes and their effect to the palaeo-environment of western Naxos island and to human activity. Detailed geomorphological mapping, study of micropaleontological and sedimentological characteristics and dating analyses of the Late Holocene of St. Georgios coastal zone were conducted.To obtain information about the Holocene stratigraphy under the recent alluvial cover, three boreholes followed the detailed geomorphological mapping. Microfaunal analysis took place and five samples of plants, shells, peat and charred material were also collected from several layers of the sedimentary sequence and were dated using AMS and conventional radiocarbon techniques providing temporal control of the sediments. The sea-land interactions during Upper Holocene, in relation to the eustatic sea level oscillations, as well as the geomorphologic observations and analysis on deposited sediments, aims to reveal the palaeo-geographic evolution of the landscape and its impact on the archaeological sites. Sea level rise along with sea-land interactions to the landscape evolution and the transgression of sea in 6144 BP have been verified.